2005
DOI: 10.1111/j.1467-8535.2005.00509.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of digital video technology in an elementary school foreign language methods course

Abstract: This article presents a case study of the use of digital video technology with a new pedagogical approach under a constructivist framework in an elementary school foreign language methods course. Data were collected through interviews with the methods course instructor, field notes, analytical notes from videotaped student presentations of their learning from the video clips, students' mid-semester evaluation of the use of video clips, and end-of-semester student reflections on open-ended questions regarding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…Persistency in technological literacy among teachers is essential for the requirements of their professions (Gorder, 2008). In educational institution, less technologically literate teachers minimize daily working of an organization (Chuang & Rosenbusch, 2005;Crowe, 2006;Goddard, 2002;Mahapatra & Lai, 2005;Thompson, 2013). Teachers' training institutions are making efforts to reshuffle their programs to manage the impending and prospective capabilities for teachers.…”
Section: Introductionmentioning
confidence: 99%
“…Persistency in technological literacy among teachers is essential for the requirements of their professions (Gorder, 2008). In educational institution, less technologically literate teachers minimize daily working of an organization (Chuang & Rosenbusch, 2005;Crowe, 2006;Goddard, 2002;Mahapatra & Lai, 2005;Thompson, 2013). Teachers' training institutions are making efforts to reshuffle their programs to manage the impending and prospective capabilities for teachers.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Godwin‐Jones (2003) indicated that video technology significantly facilitated computer‐mediated communication for language learners since it allowed for personal appearance and individual language variations. Additionally, drawing on a constructivist framework, Chuang and Rosenbusch (2005) performed an empirical study and revealed that video technology provided opportunities for inquiry‐based instruction and supported a cooperative learning environment in which students' ownership was greatly enhanced. By the same token, Wagener (2006) found that digital videos could also enhance independent learning skills.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report presents a good example of the changed role of a teacher and sheds some light on the impact of the redefinition of the role of a teacher educator on the quality of preservice teachers' experiences (Chuang & Rosenbusch, 2005). The authors analyzed a digital video project implemented in WLTE, specifically an elementary foreign language methods class.…”
Section: Projects That Model Practicementioning
confidence: 99%
“…Possibilities to exploit the potential of PBL are explained in relation to pedagogical processes and content. Although the context of WLTE has been explored, there is very little research on WLTE tasks (e.g., and even less on the use of technology on WLTE tasks (e.g., Chuang & Rosenbusch, 2005). This article discusses how some of the possibilities that PBL offers to WLTE can be operationalized and argues that providing preservice teachers experiences with and exposure to sophisticated pedagogical interventions such as the ones supported by PBL can improve the integration of technology into the design of language learning activities.…”
Section: Key Findingsmentioning
confidence: 99%
See 1 more Smart Citation